Perdida brusca de la visión ocasionada por trauma en paciente masculino. - Torres Bajaña, Pedro Wilfrido (2020)
The opacity in the transparent media of the eye is a condition that can be caused by different factors, directly to our vision, the decrease in visual acuity can be caused by different agents, one of the most frequent is by an ocular trauma. This condition can cause partial or total loss of vision in the patient if it is not assessed in time it can even cause severe damage to our vision. Your vision will be affected from the first moment you received said trauma, which is recommended to visit a person in charge of the vision. The objective of this study is to determine and specify the cause of the sudden loss of vision with the visual assessment tests, tests such as visual acuity both at a distance (6m) and near (35 - 40 cm). When we realized that the patient did not improve his visual acuity with refraction, it was possible to refer a specialist in this case to an ophthalmologist who determined that his problem was due to opacification of the transparent media, blunt degree closed ocular trauma, post-traumatic cataract, Post-traumatic uveitis, which did not allow images to reach the retina correctly.